Empowerment of Libuo District PKK Movement Team Through Business Management Training in Making Products Based on Non-Organic Waste in Sub-District Dungingi, Gorontalo City - Lanto Miriatin Amali; Rizan Machmud (AIBPM Publisher, 2019)
This Community Service Program aims to empower families and improve family welfare as well as gender equality and justice for women and men who provide time for the PKK. Proposals and problem solving methods in the Community Service program are to train as well as provide education to the PKK Mobilizing Team in an effort to manage their knowledge, experience, skills, as well as their skills in making products from non-organic waste, which can be used as added value so they can provide new business ventures and increase family income with the results of these products, especially in the Libuo village, Dungingi sub-district, Gorontalo City. The success of this activity is set at 80% of participants who take part in this training activity in order to make at the same time skilled in making non-organic waste-based products as well as gain knowledge about business management of a new business.